Nurse Decision Making and Attitudes About Circuit Disconnection During Ventilator Therapy at a Swedish Neonatal Intensive Care Unit. (December 2018) - Larsson, Christina; Karlsson, Victoria; Blomqvist, Ylva Thernström; Dowling, Donna; Thibeau, Shelley
Abstract : Background: There are many challenges to providing care to infants in need of ventilator therapy. Yet, few studies describe the practical handling of the ventilator circuit during nursing care. Purpose: To describe neonatal intensive care unit (NICU) nurses' decision making regarding whether or not to disconnect the ventilator circuit when changing the infant's position and to investigate the grounds for their decisions. Methods: A descriptive questionnaire study with both quantitative and qualitative elements was conducted. In 2015, a convenience sample of nurses working in an NICU completed a questionnaire including both closed-ended and open-ended, free-text questions. Answers to the closed-ended questions were analyzed with descriptive statistics, whereas answers to the free-text questions were analyzed using qualitative content analysis. Results: Nurses' decisions on whether to disconnect or keep the ventilator circuit closed were based on the infant's needs for ventilator support. The nurses gave several reasons and motivations both for why they disconnected the circuit and for why they did not. The handling of the circuit and the reasons and motivations given were inconsistent among the nurses. Implications for Practice: This study highlights the need for continuous, repetitive education and training for NICU nurses, as well as demonstrating the importance of clear and distinct guidelines and working methods regarding the care of infants on ventilator support. Implications for Research: Future research should continue to find ways of working and handling an infant on ventilator support that are least harmful to the infant.